2017
DOI: 10.4236/fns.2017.87053
|View full text |Cite
|
Sign up to set email alerts
|

Chemical, Nutritional, Rheological, and Organoleptical Characterizations of Stirred Pumpkin-Yoghurt

Abstract: Pumpkin contains considerable amounts of bioactive compounds which hardly valorized in dairy products. This study aims to investigate the chemical, nutritional, rheological, and organoleptical properties of prepared stirred pumpkin-yoghurt. Stirred yoghurt with three different pumpkin varieties pulp [American (AP), Domestic (DP), and Indian (IP) pumpkin] at 15% was prepared and stored at 5˚C ± 1˚C up to 14 d. The chemical properties of yoghurts include protein, fat, crude fiber, and available carbohydrates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 19 publications
11
26
0
Order By: Relevance
“…The color value of Luminosity of 113, Chrome of 6.16, h of 54.43 measured in soursop yoghurt are similar to those reported for yoghurt without fruit pulp (Nguyen and Hwang, 2016). On the other hand, soursop frozen dessert exhibited an off-white, tan color (Luminosity = 106.86, Chrome = 7.65, h = 52.84) attributable to the presence of carotenes from egg yolk employed in its formulation (Barakat and Hassan, 2017). In general, color of yoghurt and frozen dessert was not influenced (p [ 0.05) by the presence of soursop pulp.…”
Section: Physicochemical Parameterssupporting
confidence: 80%
See 1 more Smart Citation
“…The color value of Luminosity of 113, Chrome of 6.16, h of 54.43 measured in soursop yoghurt are similar to those reported for yoghurt without fruit pulp (Nguyen and Hwang, 2016). On the other hand, soursop frozen dessert exhibited an off-white, tan color (Luminosity = 106.86, Chrome = 7.65, h = 52.84) attributable to the presence of carotenes from egg yolk employed in its formulation (Barakat and Hassan, 2017). In general, color of yoghurt and frozen dessert was not influenced (p [ 0.05) by the presence of soursop pulp.…”
Section: Physicochemical Parameterssupporting
confidence: 80%
“…The effect of the addition of different types of fruit pulp as functional ingredients on the antioxidant properties of yoghurt and frozen dessert has been studied. Imanthika-Dias and Niroshan-Jayasooriya (2017) found that AOX was enhanced in yoghurt when soursop juice was added, and similar data was reported in pumpkin-flavored yoghurt (Barakat and Hassan, 2017). Citta et al (2017) investigated the oxidative changes during shelf life in lipids, proteins, and antioxidants from yoghurt supplemented with different fruits (berries, pineapple, apricot, strawberries).…”
Section: Soluble (Sp) and Hydrolysable (Hp) Polyphenols Content And Antioxidant Activity (Aox)mentioning
confidence: 71%
“…Barakat and collab. reported that there is a significant difference between the L * a * b * values and the color intensity in yogurts supplemented with pumpkin pulp [BARAKAT et al, 2017] .…”
Section: Resultsmentioning
confidence: 98%
“…The control yogurt contains 83% moisture, whereas koozha and varikka yogurts contain 81.84 and 81.67%, respectively and there is a significant difference in the moisture content of control and fruit yogurts. Barakat and Hassan (2017) reported increased moisture content in the control yogurt than the pumpkin incorporated yogurts. Matter et al (2016) also came up with a similar result when preparing cactus pear yogurt and papaya yogurts.…”
Section: Chemical Analysis Of the Yogurtsmentioning
confidence: 89%